(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
As part of this study, three distinct batches of foamed concrete were produced: plain foamed concrete (PFC), polypropylene fiber reinforced foamed concrete (PPFC), and basalt fiber reinforced foamed concrete (BFC). Compressive strength, splitting tensile strength, and, flexural strength, were some of the tests that were performed on the specimens. According to the findings of this research, using the optimal foam volume, which was determined to be 20%, results in a specific density of foam concrete that is between 342 Kg/m2and 490kg/m2and a compressive strength that ranges from 20N/mm2to 38 N/mm2. Normal concrete was combined with Styrofoam with an R-13 rating, normal concrete was combined with PFC, normal concrete was combined with PPFC, and normal concrete was combined with BFC. When compared to the PFC specimen, the flexural strength of the BFC specimen was 10 times greater. The BFC beam specimen has shown the highest load bearing capability of the RFC beam samples. In addition, the findings of the experiments indicate that the combination of conventional concrete and BFC has shown the maximum load bearing ability when bent. The combination of standard concrete and PFC has been demonstrated to have the maximum load bearing capability among the compression columns.